2020
DOI: 10.1021/acs.jpcb.9b11506
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the Human KCNQ1 Voltage Sensing Domain (VSD) in Lipodisq Nanoparticles for Electron Paramagnetic Resonance (EPR) Spectroscopic Studies of Membrane Proteins

Abstract: Membrane proteins are responsible for conducting essential biological functions that are necessary for the survival of living organisms. In spite of their physiological importance, limited structural information is currently available as a result of challenges in applying biophysical techniques for studying these protein systems. Electron paramagnetic resonance (EPR) spectroscopy is a very powerful technique to study the structural and dynamic properties of membrane proteins. However, the application of EPR sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 118 publications
0
12
0
Order By: Relevance
“…Pulsed electron-electron double resonance (PELDOR) or double electron-electron resonance (DEER) spectroscopy has been proven to be a powerful method for investigating protein structure and dynamics ( 60 , 61 , 62 , 63 ). In particular, the method has been successful in assigning conformation, oligomerization, and folding under physiological conditions or within lipid environment for a variety of membrane proteins ( 14 , 37 , 38 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 ) and is capable of offering subangstrom accuracy ( 39 , 60 ). Electron spin envelope echo modulation (ESEEM) spectroscopy has been used for measuring site-specific deuterium (solvent) accessibility in membrane proteins ( 14 , 73 , 74 , 75 ), and the method is a valuable tool for identifying lipid/detergent buried or exposed membrane protein sites.…”
Section: Introductionmentioning
confidence: 99%
“…Pulsed electron-electron double resonance (PELDOR) or double electron-electron resonance (DEER) spectroscopy has been proven to be a powerful method for investigating protein structure and dynamics ( 60 , 61 , 62 , 63 ). In particular, the method has been successful in assigning conformation, oligomerization, and folding under physiological conditions or within lipid environment for a variety of membrane proteins ( 14 , 37 , 38 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 ) and is capable of offering subangstrom accuracy ( 39 , 60 ). Electron spin envelope echo modulation (ESEEM) spectroscopy has been used for measuring site-specific deuterium (solvent) accessibility in membrane proteins ( 14 , 73 , 74 , 75 ), and the method is a valuable tool for identifying lipid/detergent buried or exposed membrane protein sites.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have successfully demonstrated the use of synthetic polymers to directly extract membrane proteins and reconstitute them in near-native lipid bilayer nanodiscs without using a detergent. [1][2][3][4][5][6][7] However, the presence of charge on the currently known polymers drastically limits their applications. [8,9] The high charge density of the polymer interferes with the purification by ion-exchange chromatography and also detrimental to study oppositely charged membrane proteins due to charge-charge interactions.…”
mentioning
confidence: 99%
“…However, no membrane mimetic systems are universally compatible to all membrane proteins requiring rigorous time-consuming optimization processes for their incorporation in a suitable membrane environment. Currently available and widely used membrane mimetic systems are detergent micelles, bicelles, liposomes, lipodiscs, and lipodisq nanoparticles/SMALPs (styrene maleic acid lipid particles) [12][13][14][15][16]. These membrane mimetic systems have their own benefits and limitations.…”
Section: Membrane Proteinsmentioning
confidence: 99%
“…Another recent example of the application of nitroxide based DEER spectroscopy is the study of the Human KCNQ1 voltage sensing domain (Q1-VSD) in lipodisq nanoparticles [14]. Human KCNQ1 is a voltage-gated potassium channel modulated by members of the KCNE protein family.…”
Section: Distance Measurement On Membrane Proteins Using Dual Sdsl Epmentioning
confidence: 99%
See 1 more Smart Citation